Dosimetric study for cervix carcinoma treatment using intensity modulated radiation therapy (IMRT) compensation based on 3D intracavitary brachytherapy technique - Yin, Gang; Wang, Pei; Lang, Jinyi; Tian, Yin; Luo, Yangkun; Fan, Zixuan; Tam, Kin Yip (Journal of Contemporary Brachytherapy, 2016)
Purpose : Intensity modulated radiation therapy (IMRT) compensation based on 3D high-dose-rate (HDR) intracavitary brachytherapy (ICBT) boost technique (ICBT + IMRT) has been used in our hospital for advanced cervix carcinoma patients. The purpose of this study was to compare the dosimetric results of the four different boost techniques (the conventional 2D HDR intracavitary brachytherapy [CICBT], 3D optimized HDR intracavitary brachytherapy [OICBT], and IMRT-alone with the applicator in situ). Material and methods: For 30 patients with locally advanced cervical carcinoma, after the completion of external beam radiotherapy (EBRT) for whole pelvic irradiation 45 Gy/25 fractions, five fractions of ICBT + IMRT boost with 6 Gy/fractions for high risk clinical target volume (HRCTV), and 5 Gy/fractions for intermediate risk clinical target volume (IRCTV) were applied. Computed tomography (CT) and magnetic resonance imaging (MRI) scans were acquired using an in situ CT/MRI-compatible applicator. The gross tumor volume (GTV), the high/intermediate-risk clinical target volume (HRCTV/IRCTV), bladder, rectum, and sigmoid were contoured by CT scans. Results: For ICBT + IMRT plan, values of D 90 , D 100 of HRCTV, D 90 , D 100 , and V 100 of IRCTV significantly increased (p < 0.05) in comparison to OICBT and CICBT. The D 2cc values for bladder, rectum, and sigmoid were significantly lower than that of CICBT and IMRT alone. In all patients, the mean rectum V 60 Gy values generated from ICBT + IMRT and OICBT techniques were very similar but for bladder and sigmoid, the V 60 Gy values generated from ICBT + IMRT were higher than that of OICBT. For the ICBT + IMRT plan, the standard deviations (SD) of D 90 and D 2cc were found to be lower than other three treatment plans. Conclusions : The ICBT + IMRT technique not only provides good target coverage but also maintains low doses (D 2cc ) to the OAR. ICBT + IMRT is an optional technique to boost parametrial region or tumor of large size and irregular shape when intracavitary/interstitial brachytherapy cannot be used.